Training to Foster a Positive Work Culture for Improving Teacher Performance at SMA Dwi Warna - Agung Solihin; Achmad Tarmizi (Abdimas Paspama, 2025)
This community service program aims to improve teacher performance at SMA Dwi Warna by strengthening a positive work culture. The initiative was carried out through interactive training, group discussions, and ongoing coaching designed to build awareness and commitment among educators. Preliminary observations indicated challenges such as lack of motivation, ineffective communication, and inconsistency in collaborative practices. The training sessions addressed these issues by emphasizing core values such as integrity, responsibility, teamwork, and professional commitment. The program successfully fostered a more cohesive and reflective work environment. Teachers demonstrated increased awareness and willingness to apply positive work ethics in their daily responsibilities. As a result, a weekly reflection forum was established to encourage continuous dialogue and shared learning. This initiative highlights the importance of sustained efforts in cultivating a positive work culture, suggesting that such interventions can significantly contribute to the overall improvement of educational quality and institutional performance.